Hyaluronan preconditioning of monocytes/macrophages affects their angiogenic behavior and regulation of TSG‐6 expression in a tumor type‐specific manner. (16th May 2019) - Spinelli, Fiorella M.; Vitale, Daiana L.; Icardi, Antonella; Caon, Ilaria; Brandone, Alejandra; Giannoni, Paula; Saturno, Virginia; Passi, Alberto; García, Mariana; Sevic, Ina; Alaniz, Laura
Abstract : Hyaluronan is a glycosaminoglycan normally present in the extracellular matrix in most tissues. Hyaluronan is a crucial player in many processes associated with cancer, such as angiogenesis, invasion, and metastasis. However, little has been reported regarding the action of hyaluronan on monocytes/macrophages (Mo/MØ) in tumor angiogenesis and its consequences on tumor development. In the present study, we investigated the effects of hyaluronan of different sizes on human Mo/MØ angiogenic behavior in colorectal and breast carcinoma. In vitro, the treatment of Mo/MØ with lysates and conditioned media from a breast but not from colorectal carcinoma cell line plus high‐molecular weight hyaluronan induced: (a) an increased expression of angiogenic factors VEGF, IL‐8, FGF‐2, and MMP‐2, (b) an increased endothelial cell migration, and (c) a differential expression of hyaluronan‐binding protein TSG‐6. Similar results were observed in Mo/MØ derived from breast cancer patients treated with tumor lysates. Besides, macrophages primed with high‐molecular weight hyaluronan and inoculated in human breast cancer xenograft tumor increased blood vessel formation and diminished TSG‐6 levels. In contrast, the effects triggered by high‐molecular weight hyaluronan on Mo/MØ in breast cancer context were not observed in the context of colorectal carcinoma. Taken together, these results indicate that the effect of high‐molecular weight hyaluronan as an inductor of the angiogenic behavior of macrophages in breast tumor context is in part consequence of the presence of TSG‐6. Abstract : Hyaluronan is a crucial player in many processes associated with cancer. Here, we investigated the action of hyaluronan (high‐ or low‐molecular weight) on monocytes/macrophages (Mo/MØ) in different tumor contexts. Our findings suggest that treatment with high‐molecular weight hyaluronan modulates TSG‐6 protein levels and increases the angiogenic behavior of Mo/MØ in the context of breast but not of colorectal carcinoma.